An ecological systems approach to the difficulties faced by social workers in community home-based care organisations for people living with HIV - Maditobane Robert Lekganyane; Tsakani Salphinah Manganyi (Health Psychology and Behavioral Medicine, 2023)
ABSTRACTBackground: Social workers play an instrumental role in supporting vulnerable populations by among others, designing and implementing support programmes such as community home-based care (CHBC) for People Living with HIV (PLWHIV). Existing research studies have demonstrated their role in championing programmes like support groups, counselling services and material support to PLWHIV and their caregivers as well as the HIV prevention and other advocacy programmes across communities. Within the CHBC programmes for HIV, social workers’ roles include supporting caregivers who care for PLWHIV to manage complex cases that are beyond their competencies and offering the necessary training on patient support. Although the contributions made by social workers in the field of HIV have immensely been documented in various parts of literature, less substantial attention has been given to their challenges particularly when working with PLWHIV through CHBC programmes.Methods: This qualitative research study was designed from exploratory and descriptive strategies and grounded on ecological systems theory to explore the challenges faced by social workers working with PLWHIV through the CHBC programmes. Thirteen social workers were sampled from South Africa’s City of Tshwane Municipality (CTMM) through purposive and snowball techniques, to participate in semi-structured interviews of which the data were analysed thematically and verified according to Lincoln and Guba’s data qualitative data verification strategies.Findings: The findings highlighted several difficulties faced by social workers including difficulties associated with managing challenges faced by PLWHIV, dealing with uncooperative PLWHIV and lack of resources to effectively respond to their clients’ needs.Conclusions: The conditions in which social workers render services to PLWHIV were highlighted by pointing to the complexities resulting from these challenges which further compromises the quality of services rendered to PLWHIV. For the success of HIV programmes, it is essential to support social workers through training, resources, community awareness and income-generating projects.